EFFECT OF IT GOVERNANCE, CONTINUOUS AUDITING AND IT GOALS ALIGNMENT TO COMPANY’S PERFORMANCE (Study on Plantation Companies in the Group of PT. Astra Agro Lestari Tbk in Riau) - Nafisah Syafei (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
The purpose of this study is to examine the effect of IT governance, continuous auditing, and the IT goals alignment to company’s performance. This study also examined the effect of IT governance to IT goals alignment, the effect of IT governance to continuous auditing, and the effect of IT goals alignment to continuous auditing. Research conducted on the plantation companies in the group of PT. Astra Agro Lestari, Tbk in Riau that have used the information system ERP (Enterprise Resource Planning) to integrate and automate business processes. Population of this study included all managers in these plantation companies. Sampling was conducted by purposive sampling that take samples from thecertain level managers who are in the top level of main structure of the six companies in these companies plantation group. Data processing is done to 40 questionnaires returned byrespondents using PLS analysis (Partial Least Square). Results of hypothesis testing at the 0.05 significance level indicates that the IT governance, continuous auditing, and the IT goals’s alignment affect the company's performance. IT governance affects on the IT goals’s alignment and IT governance also affect on the continuous auditing, while the alignment of IT goals has no effect on continuous auditing.